1990
DOI: 10.1136/bmj.301.6765.1379
|View full text |Cite
|
Sign up to set email alerts
|

Health care screening for people with mental handicap living in the community.

Abstract: Objective-To determine what contact people with mental handicap had had with their general practitioner in the previous year; what prescribed drugs they were taking and whether these had been reviewed; when hearing and vision had last been screened; and what medical problems were found on examination.Design-Case series. Setting-Day centre for adults with mental handicap.Subjects-A balanced sample of 75 of the 150 people attending the day centre. 10 Were excluded because consent was not given.Results-The subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
180
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(193 citation statements)
references
References 4 publications
10
180
1
1
Order By: Relevance
“…Physical disorders reported in adults with learning disabilities, with relatively high prevalence rates include, obesity (45% in the study by Wilson and Haire, 1990), sensory impairment (hearing 20%, ocular pathology 49% in study by Larson and Lapointe, 1986) and epilepsy (Jacobson and Janicki, 1985). In this study 81% of individuals examined were found to be overweight or obese (BMI >24), significant impaired vision was present in 18% and significant impaired hearing in 12% of those examined.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Physical disorders reported in adults with learning disabilities, with relatively high prevalence rates include, obesity (45% in the study by Wilson and Haire, 1990), sensory impairment (hearing 20%, ocular pathology 49% in study by Larson and Lapointe, 1986) and epilepsy (Jacobson and Janicki, 1985). In this study 81% of individuals examined were found to be overweight or obese (BMI >24), significant impaired vision was present in 18% and significant impaired hearing in 12% of those examined.…”
Section: Discussionmentioning
confidence: 74%
“…Evidence demonstrating the need for an assessment of medical problems for adults with Down syndrome is available from two sources; findings for people with learning disability as a whole (Jacobson and Janicki, 1985;Wilson and Haire, 1990) and from findings for children with Down syndrome (Howells, 1989;Cooley and Graham, 1991). However, extrapolation of findings from these groups to adults with Down syndrome is inappropriate and likely to be inaccurate.…”
Section: Introductionmentioning
confidence: 99%
“…15 Such individuals may have undiagnosed systemic disease, 9,11 be infrequently reviewed by their general medical practitioners 9 and possibly be prescribed inappropriate medication. 9 One US study even found that the mortality rates of individuals with developmental disabilities increased following transfer from state hospital institutions to community care. 16 Nevertheless people with disabilities do benefit when being transferred from long-stay hospitals to the community.…”
Section: Discussionmentioning
confidence: 99%
“…There have, however, been concerns regarding the subsequent degree of access to community-based services, including healthcare facilities. 9,10 For, example, in one study 106 of 191 adults with learning disabilities who had been living in the community were examined and found to have at least one unattended but treatable medical condition. 11 Little is known of the effects of community-based living upon oral health and the availability of dental services for those people who have left long-stay institutions.…”
mentioning
confidence: 99%
“…27 Therefore clinical symptoms may not be associated with a physical or mental illness by those caring for individuals with a intellectual disability. 28 With frequent changes in carers, having a baseline annual health check ensures that an individual's health can be monitored, and helps also with the problem of detecting and reporting any change in the symptoms of individuals with intellectual disabilities over time. 29 Legislation and policy, including The Health and Social Care Act (2008) 30 and 'Valuing people now' strategy (2009), 31 indicate that an integrated interprofessional approach to providing healthcare must be adopted if barriers, including inaccessible information, are to be overcome and the best outcomes achieved.…”
Section: Deficiencies / Inequalities In Access To Healthcarementioning
confidence: 99%